De-Islamization in Java during the Dutch colonial period from 1800 to 1942 - Priyoyudanto, Febri (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
A very long period of Dutch colonialism in Indonesia still has a very significant impact on Indonesia, including Java as a part of Nusantara. Javanese people as the largest population in Indonesia were greatly affected of a de-Islamization process during the Dutch colonial period. This process not only made Javanese people estranged from Islamic values, but also, the culture of Hindu-Buddhism is still seen as a major variable in Javanese culture. Although, the Dutch colonists persuade systematic de-Islamization efforts, Javanese Muslims provided the resistance in many ways to prevent it. This thesis intends to elaborate and analyze the de-Islamization efforts in Java during the Dutch colonial period. The thesis will focus on the Javanese ethnic group on Java Island, Indonesia. This thesis will be useful in understanding the patterns and strategy for de-Islamization which were created by the Dutch during the colonial period. The method of data collection used in this thesis is documentary research. The information was gathered from books, journals, and websites pertaining to the Dutch colonial history of Java will be utilized. In order to enhance comprehension of this thesis, the author will survey Javanese culture, educational and cultural de-Islamization, Islamic revivalism and resistance political de-Islamization in Java during the Dutch colonial period.